2006
DOI: 10.1007/s11547-006-0111-7
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructed urinary bladder following radical cystectomy for bladder cancer. Multidetector CT evaluation of normal findings and complications

Abstract: MDCT of the contrast-filled neobladder is useful for the morphological and, in part, functional evaluation of the neobladder during postoperative follow-up and helps detect surgical complications. Radiation protection concerns do not, however, support the routine use of the method, even if the MDCT data are in part correlated to the urodynamic data and may in many cases provide a morphological explanation to the presence of functional alterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…A mixture of contrast material (Diatrizoate Meglumine, Cystografin 1 , Bracco Diagnostics Inc., Princeton, NJ) and saline was instilled until the patient had the subjective sensation of a full bladder and according with the volume reported in the voiding diary. 3 The patients were then scanned caudal to cranial from the pelvic floor to the level of the third lumbar vertebra using slice model (thickness 5 mm, reconstruction interval 5 mm,140 kV and 250 mA) The 5 mm CT scan section obtained with our scan protocol were transferred to an external workstation (Voxar 1 , Edinburgh, Scotland, now Barco Inc.) where the 3D reconstruction process (Multiplanar reconstructed images or MPR, volume rendering and virtual endoscopic evaluation of the contrast-filled neobladder) was performed. The main focus was on identification of several anatomical parameters: the distance from the center of the neobladder to the symphisis (DPS), to the coccyx line (DC), to the femor head bilaterally (DRF, DLF), the volume calculated by the software using the 3D reconstruction (V), the sphericity as a way to measure the symmetrical shape of the neobladder, calculated as caudocranial diameter þ anteroposterior diameter/latero-lateral diameter (SP), the neovesical-urethral angle measured as the intersection of lines drawn along the dorsal margin of the urethra and the posterior floor of the neobladder (NVUA), recesses (R), internal folds (IF), vesico-ureteral reflux (RE), and the thickness of the neobladder wall (TH) (see Figs.…”
Section: Ct Scanmentioning
confidence: 99%
“…A mixture of contrast material (Diatrizoate Meglumine, Cystografin 1 , Bracco Diagnostics Inc., Princeton, NJ) and saline was instilled until the patient had the subjective sensation of a full bladder and according with the volume reported in the voiding diary. 3 The patients were then scanned caudal to cranial from the pelvic floor to the level of the third lumbar vertebra using slice model (thickness 5 mm, reconstruction interval 5 mm,140 kV and 250 mA) The 5 mm CT scan section obtained with our scan protocol were transferred to an external workstation (Voxar 1 , Edinburgh, Scotland, now Barco Inc.) where the 3D reconstruction process (Multiplanar reconstructed images or MPR, volume rendering and virtual endoscopic evaluation of the contrast-filled neobladder) was performed. The main focus was on identification of several anatomical parameters: the distance from the center of the neobladder to the symphisis (DPS), to the coccyx line (DC), to the femor head bilaterally (DRF, DLF), the volume calculated by the software using the 3D reconstruction (V), the sphericity as a way to measure the symmetrical shape of the neobladder, calculated as caudocranial diameter þ anteroposterior diameter/latero-lateral diameter (SP), the neovesical-urethral angle measured as the intersection of lines drawn along the dorsal margin of the urethra and the posterior floor of the neobladder (NVUA), recesses (R), internal folds (IF), vesico-ureteral reflux (RE), and the thickness of the neobladder wall (TH) (see Figs.…”
Section: Ct Scanmentioning
confidence: 99%
“…Several imaging studies used computed tomography and static MRI to evaluate postoperative anatomy and functional aspects of the neobladder [9,[15][16][17][18] . One of these studies showed that the location of the neobladder neck in the pelvis has an important impact on voiding: in patients showing good void competence the neobladder neck is located at the most caudal portion of the pouch [17] .…”
Section: Discussionmentioning
confidence: 99%
“…A number of complications can occur following the construction of an orthotopic neobladder, including urine incontinence, pyelonephritis (7.4%), stricture at the ileourethral or ileoureteral anastomosis sites (3.3 and 3%, respectively), as well as neobladder-enteral fistulas (1.1%) [8][9][10] . Haematuria may present during follow-up as a result of an upper urinary tract recurrence of the primary bladder cancer, which has been reported in up to 6% of cases [5] , pouch infection and stones [11] .…”
Section: Discussionmentioning
confidence: 99%